Comparative Study Between Dexmeditomidine and Midazolam for Prevention of Emergence Agitation After Nasal Surgery - Rukhsar Shaw; Arti Mahajan; Rajdeep Kour; Anjali Mehta; Renu Wakhloo (JK Science, 2022)
Background: Emergence agitation (EA) is a common complication that develops in the postanaesthesia care unit (PACU). It usually occurs between initial 30- and 60-minute following emergence from anaesthesia and may last upto 45 min to 48 hours in extreme cases. Aims and Objective: Objective of the study was to compare incidence of emergence agitation, hemodynamic parameters, sedation score between dexmedetomidine and midazolam after nasal surgeries. Material & Methods: This prospective, comparative study was conducted in 60 patients of age 18-60 years, ASA grade I and II scheduled for elective nasal surgeries. Patients were randomly divided into two groups: Group D received injection Dexmedetomidine loading dose of 0.5mcgm/kg i.v over 15 minutes and then 0.1 mcg/kg/hour i.v as maintenance infusion Group M received injection Midazolam- loading Dose 0.05mg/kg i.v over 15 minutes and then 0.05 mg/kg/ hour i.v as maintenance infusion. Results: There was no significant difference in sex, age, height and weight of the patients between two groups (p>0.05). Incidence of agitation was more in group M (43.33%) as compared to group D (23.33%) but the difference was statistically insignificant (p = 0.110). Maximum no. of patients in Group D had Riker Sedation- Agitation Scale (RSAS) score 4 which was taken as ideal with no agitation and drowsiness as compare to group M. There was no significant difference in MAP in both groups, the incidence of hypotension and decrease in heart rate was more in group D as compare to group M Conclusion: Midazolam and Dexmeditomidine were comparable when given as infusion for prevention of emergence agitation after nasal surgeries.